2014
DOI: 10.1111/evj.12267_86
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Three Dimensional Modelling of Mutant Glycogen Synthase Associated with Equine Type 1 Polysaccharide Storage Myopathy

Abstract: This publication is a compilation of all Research Abstracts presented at the Ninth International Conference on Equine Exercise Physiology. Unlike previous ICEEP conferences there will not be a conference proceedings of full length manuscripts. These abstracts succinctly summarise a wide array of investigations relevant to the equine athlete, and will be useful to veterinarians and others involved in management of horses used for sport, work and competition. The abstracts encompass the topics of Applied Physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Glycogen synthase activity was significantly higher in PSSM1 homozygotes than in heterozygotes and control horses but was not associated with increased expression or degradation of the mutant enzyme. Subsequent in silico 3‐dimensional (3D) modelling of mutant GS associated with PSSM1 revealed that although the PSSM1 mutation lay close to the G6P binding site, it did not confer any clear structural rearrangement on the 3D configuration of the protein .…”
Section: Muscle Physiologymentioning
confidence: 99%
“…Glycogen synthase activity was significantly higher in PSSM1 homozygotes than in heterozygotes and control horses but was not associated with increased expression or degradation of the mutant enzyme. Subsequent in silico 3‐dimensional (3D) modelling of mutant GS associated with PSSM1 revealed that although the PSSM1 mutation lay close to the G6P binding site, it did not confer any clear structural rearrangement on the 3D configuration of the protein .…”
Section: Muscle Physiologymentioning
confidence: 99%